Determinants Of Growth In Algerian - Hebboul, Mohamed (جامعة الوادي University of Eloued, 2025)
The aim of this study was to identify the factors influencing the growth of Algeria's non-hydrocarbon export value during the period from 1990 to 2023, through an empirical analysis based on the (ARDL) methodology . The measurement results indicated a long-term equilibrium relationship (cointegration) between Algeria's non-hydrocarbon exports and a set of explanatory variables included in the estimated model, namely: the real exchange rate, financial development, private domestic investment, government investment expenditure, and per capita GDP. A significant and positive relationship was recorded for these variables with the value of nonhydrocarbon exports from Algeria, except for the last two variables, which showed no significant effect due to the lack of significance in the relationship over both short and long terms, The short-term rate of correction of imbalances to return to balance reached 135% (less than a year). Furthermore, it was found that financial development is the most important determinant of the value of Algeria's non-hydrocarbon exports, followed by the real exchange rate and then private domestic investment in both the short and long terms.
Determinants of growth in Algerian non-hydrocarbon exports during the period (1990-2023) An econometric study using the autoregressive distributed lag (ARDL) model
مقال
Keywords: Exports; non-hydrocarbon exports; export diversification; Algeria; ARDL model.